Dominant Frequency and Power Spectral Density Analysis for Determining the Location of Earthquake Shelters in the Rukoh Dam, Pidie - Jihad, Abdi; Ardiyansyah, Tommy; Al Atas, Zaenal Abidin; Fajaruddin, Fajaruddin; Rusdin, Andi Azhar; P. N., T. Agus Putra (Jurnal Inovasi Konstruksi, 2025)
Seismic activity around the Rukoh Dam, Pidie Regency, Aceh Province, is affected by two active fault systems, the Aceh Fault and the Seulimeum Fault. This condition requires a detailed study of soil response characteristics to support earthquake-resistant infrastructure planning, especially in determining the location of earthquake shelters. This study aims to evaluate the suitability of three potential earthquake shelter locations around the Rukoh Dam using microtremor data. Meanwhile, data analysis was carried out using the Horizontal to Vertical (H/V) spectral ratio method to determine the dominant frequency of the soil (Fo) and Power Spectral Density (PSD) to assess the characterization of the location. The results of the analysis showed that Point 1 had the highest Fo (5.0 Hz) and the shallowest sediment thickness (~15 m) which indicated stiff soil conditions and low seismic amplification potential. In contrast, points 2 and 3 showed lower Fo (2.0 Hz and 1.6 Hz, respectively) with a sediment thickness of 35 m, indicating a higher risk of amplification. Point 1 is recommended as a permanent shelter location, while points 2 and 3 require structural strengthening or alternative utilization.